International business transactions fundamentals - Brand, Ronald A. (Kluwer Law International B. V., 2019)
International Business Transactions Fundamentals' identifies the many sources of risk in cross-border transactions, analyzes in great depth the legal instruments that provide protection to the parties, and describes the practical means of reducing, reallocating, and eliminating risks. Designed primarily as a casebook and text for law school study, this volume represents nearly four decades of work by the author to present the fundamentals of the law of international business transactions. The coverage of this second edition remains consistent with the first edition, with one notable exception where the chapter on taxation of international transactions has been omitted. Like the first edition, this second edition focuses on the role of lawyers in identifying risks inherent in cross-border economic transactions, and then using primarily the law and negotiations to eliminate where possible, reduce where practicable, and reallocate where necessary those risks to the benefit of the client.